2009
DOI: 10.1007/s00223-008-9205-7
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized Dentin Matrix Acts as a Scaffold for Repair of Articular Cartilage Defects

Abstract: Articular cartilage repair remains a major obstacle in tissue engineering. In the present study, we investigated the potential for demineralized dentin matrix (DDM; organic material derived from dentin) obtained from extracted teeth to be used as bone graft material. To evaluate the extent to which DDM induces osteochondral regeneration, we implanted DDM from bovine teeth in rabbit knees with full-thickness articular cartilage defects. Thirty-three 13-week-old male rabbits weighing 2.5-3.0 kg were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…It has also been clarified that demineralized dentin originating from various mammals induces undifferentiated mesenchymal cells to differentiate into osteogenic cells and then into cartilage and bone 23) . Although Reddi documented osteoinduction with particle sizes of 74 to 420 µm 24,25) , our previous study demonstrated particle sizes of 250 to 500 µm were highly efficient in osteoinduction 7) . In the present study, to ensure post-grafting stability, the particle size of DDM was set at 250 to 500 µm.…”
Section: Ddmmentioning
confidence: 73%
See 2 more Smart Citations
“…It has also been clarified that demineralized dentin originating from various mammals induces undifferentiated mesenchymal cells to differentiate into osteogenic cells and then into cartilage and bone 23) . Although Reddi documented osteoinduction with particle sizes of 74 to 420 µm 24,25) , our previous study demonstrated particle sizes of 250 to 500 µm were highly efficient in osteoinduction 7) . In the present study, to ensure post-grafting stability, the particle size of DDM was set at 250 to 500 µm.…”
Section: Ddmmentioning
confidence: 73%
“…In order to make the particle size even, DDM with particle sizes of 250 -500 mm was collected by sieving ( Fig. 1) 7) .…”
Section: Ddm Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has also been reported that DSp is essential for growth and maintenance of mandibular condylar cartilage [42]. Although it is well known that dentin sialophosphoprotein plays an important role in the mineralization of hard tissues such as bone and teeth, demineralized dentin matrices have been shown to function as efficient scaffolds for cartilage repair [43,44]. Moreover, dentin sialophosphoprotein belongs to the family of small integrin binding ligands (SIBLING) which have several factors common with matrix extracellular phosphoglycoproteins [45].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that BP administration near the extraction socket and extraction site and below the maxillary periosteum on the opposite side improved the osteochondral repair ability of the extraction socket [9][10][11] . However, it is unclear whether or not direct BP administration to the defective bone region exhibits a similar effect.…”
Section: Introductionmentioning
confidence: 99%